THE INFLUENCE OF READING HABIT ON THE STUDENTS ACHIEVEMENT IN LITERARY RELATED SUBJECTS : A RESEARCH REPORT - Heny Hartono; Marini Pauli; Antonius Suratno (Celt: A Journal of Culture, English Language Teaching & Literature, 2005)
This article is a research report about the influence of English reading habit on the students achievement in literary related subjects: Prose 1, Prose 2, Drama 1, Drama 2, and Poetry Analysis. There are two variables in this research: the English reading habit as independent variable and students achievement as dependent variable. The data are obtained through questionnaire, documentation and interview. Furthermore, it is analyzed using Product-Moment Correlation. The result of Product-Moment Correlation shows that there is a correlation between English reading habit and students achievement on those subjects. The result shows that the score of correlation Product-Moment is higher than score of r-table, that is 0,401455>0.339. It is found that determinant coefficient is 0.161167, which means the influence of English reading habit on the students achievement is 16.12%. It indicates that English reading habit is not the most dominant factor which influences students achievement in those subjects. In other words, the increase of students achievement is not only determined by their reading habit, but also influenced by other factors, such as intelligence, aptitude, motivation, school and family environment, teachers, and facilities including books and libraries.